2022
DOI: 10.3390/molecules28010015
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Directly Affect Hyaluronan Production of Orbital Fibroblasts; A Potential Pleiotropic Effect in Graves’ Orbitopathy

Abstract: Orbital connective tissue expansion is a hallmark of Graves’ orbitopathy (GO). In moderate-to-severe active GO, glucocorticoids (GC) are the first line of treatment. Here we show that hydrocortisone (HC), prednisolone (P), methylprednisolone (MP), and dexamethasone (DEX) inhibit the hyaluronan (HA) production of orbital (OF) and dermal (DF) fibroblasts. HA production of GO OFs (n = 4), NON-GO OFs (n = 4) and DFs (n = 4) was measured by ELISA. mRNA expression of enzymes of HA metabolism and fibroblast prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that leukoregulin, IL-1, TNF-α, IFN-γ, TGF-β, IGF-1, PDGF and prostaglandins enhance HA synthesis in GO fibroblasts. Hyaluronic acids could induce MAPK and NF-κB phosphorylation; while HA-induced transcription of COX-2 was halted by the administration of MAPK or NF-κB inhibitors [ 30 , 31 , 32 , 33 ] and inhibited by methylprednisolone and dexamethasone. Additionally, HA synthesis could be stimulated by adipogenesis.…”
Section: Hyaluronan Formation By Orbital Fibroblastsmentioning
confidence: 99%
“…It has been reported that leukoregulin, IL-1, TNF-α, IFN-γ, TGF-β, IGF-1, PDGF and prostaglandins enhance HA synthesis in GO fibroblasts. Hyaluronic acids could induce MAPK and NF-κB phosphorylation; while HA-induced transcription of COX-2 was halted by the administration of MAPK or NF-κB inhibitors [ 30 , 31 , 32 , 33 ] and inhibited by methylprednisolone and dexamethasone. Additionally, HA synthesis could be stimulated by adipogenesis.…”
Section: Hyaluronan Formation By Orbital Fibroblastsmentioning
confidence: 99%